The prevalence trends of Trichomonas vaginalis infection among women in Jingzhou, central of China, 2019–2023 - Yang, Yan; Qu, Yue; Yan, Bin; Wang, Changzheng; Liu, Shun (BMC infectious diseases, 2025)
Trichomonas vaginalis (T. vaginalis) is one of the most prevalent sexually transmitted infections globally, with significant regional variations in its prevalence. This study aimed to examine the epidemiological characteristics of T. vaginalis infection in Jingzhou, Hubei Province, China. To obtain the prevalence of T. vaginalis infection among age groups and different years, a total of 115,775 patients from 2019 to 2023 were included in this study. Two detection methods including immunochromatographic assay and wet mount microscopy were used to detect the pathogens in vaginal swabs samples including T. vaginalis with other vaginal pathogens, such as Candida albicans (C. albicans) and Gardnerella Vaginalis (G. vaginalis). The overall prevalence of T. vaginalis in Jingzhou was 3.41%, demonstrating a decreasing trend from 2019 to 2023, with a particularly significant decrease during the COVID-19 pandemic in 2020-2022 (P < 0.001). The highest positive rate of T. vaginalis was observed in the 45-54 years age group (4.87%), while the lowest rate was observed in the 25-34 years age group (2.37%). The prevalence of T. vaginalis in pregnant women (0.83%) was lower than that in non-pregnant women (1.87%), with a statistically significant difference (P < 0.001). T. vaginalis had co-infection with other pathogens (2.76%) compared to single infection (0.65%), and the most common co-infection pattern was T. vaginalis and G. vaginalis (2.09%). The results showed that there was relative high consistency (Kappa: 0.841) between the immunochromatographic assay and wet mount microscopy method for the detection of T. vaginalis. Additionally, elevated leukocyte levels were associated with a higher prevalence of T. vaginalis. The overall infection rate of T. vaginalis was 3.41%, showing a decreasing trend in prevalence in Jingzhou from 2019 to 2023. The prevalence was the highest in the 45-54 years age group. The study suggested that the immunochromatographic assay should be widely implemented as a screening method for T. vaginalis in primary healthcare facilities.